The White Dwarf Binary Pathways Survey −III. Contamination from hierarchical triples containing a white dwarf. Issue 1 (18th March 2020) - Lagos, F; Schreiber, M R; Parsons, S G; Zurlo, A; Mesa, D; Gänsicke, B T; Brahm, R; Caceres, C; Canovas, H; Hernandez, M-S; Jordan, A; Koester, D; et al.
ABSTRACT: The White Dwarf Binary Pathways Survey aims at increasing the number of known detached A, F, G, and K main-sequence stars in close orbits with white dwarf companions (WD+AFGK binaries) to refine our understanding about compact binary evolution and the nature of Supernova Ia progenitors. These close WD+AFGK binary stars are expected to form through common envelope evolution, in which tidal forces tend to circularize the orbit. However, some of the identified WD+AFGK binary candidates show eccentric orbits, indicating that these systems are either formed through a different mechanism or perhaps they are not close WD+AFGK binaries. We observed one of these eccentric WD+AFGK binaries with SPHERE and find that the system TYC 7218-934-1 is in fact a triple system where the WD is a distant companion. The inner binary likely consists of the G-type star plus an unseen low-mass companion in an eccentric orbit. Based on this finding, we estimate the fraction of triple systems that could contaminate the WD+AFGK sample. We find that less than 15 per cent of our targets with orbital periods shorter than 100 d might be hierarchical triples.